Dimensionamento e avaliação do potencial de arrefecimento de edificação de ensino através de ventilação por efeito chaminé em Santa Maria - RS - Christmann, Laura Landerdahl (2015)
Natural ventilation is recognized by the scientific community as an important strategy for the promotion of thermal comfort. It s application in real situations, however, is extremely low, which is believed to be due to the lack of specific information as well as the lack of reliability in the success of these strategies. The present study aimed to propose, measure and evaluate natural ventilation strategy. It was defined the ventilation through the chimney effect for multiple floors educational buildings, disregarding the wind incidence, in the city of Santa Maria, RS, Bioclimatic Zone 2. Eight sizes of frames combinations have been proposed to be analyzed. Simulations with all openings combinations were made through DesignBuilder software. Based on the simulations results, it was calculated the maximum possible wind speeds through the strategy. Obtained such values, it was possible to analyze the thermal comfort gains with the different combinations of frames. It sets up, as the most suitable design and better performance, the use of all the frames in the same size, this being equivalent to 5,71% of the floor area. Analyzing through adaptive comfort, such configuration has resulted in reduction of degree-hour of discomfort in 27,9%, 33,3%, 38,8% and 42.7% for one floor, two floors, three floors and four floors building, respectively, comparing to the building without the use of the strategy. Since the results for the analyzed situation, compared to the recommended values by normatives for thermal confort condition, the strategy is evaluate as good potential and easily aplication in real situations.